Individual Differences and Psychosis-Risk Screening: Practical Suggestions to Improve the Scope and Quality of Early Identification - Schiffman, Jason; Ellman, Lauren M.; Mittal, Vijay A. (Frontiers in Psychiatry, 2019)
Approaches to identifying individuals at clinical high-risk (CHR) for psychosis currently do not carefully weigh considerations around individual differences. Effective identification depends on awareness of factors beyond psychopathology as it is reflected in the current literature, such as sensitivity to idiographic circumstances and individual differences. The inability to address contextual factors when employing the status quo method of identification likely contributes to the unacceptably poor accuracy when identifying people at CHR. Individual differences related to factors such as culture, race, comorbidity, and development likely play an important role in accurate identification, and have the potential to improve the validity of approaches intended to identify this population. Tailored approaches to assessment based on an awareness of context, identity, setting, and preferences of clients are possible, and customizing assessment efforts accordingly may be useful for accurate identification of people at CHR. Highlighting the potential for the existing early identification paradigm to marginalize or misunderstand certain groups, we describe how effective identification and ethical diagnosis require sensitivity to individual differences writ large. We suggest that recognizing the importance of these factors advances a more inclusive and accurate approach to identification.